2019
DOI: 10.1017/s1751731118003476
|View full text |Cite
|
Sign up to set email alerts
|

Review: Proteomic approaches to control lactational parameters in dairy cows

Abstract: The use of a proteomic approach to investigate changes in the milk proteome is growing and has parralleled the increasing technological developments in proteomics moving from early investigation using a gel-based two-dimensional separation approach to more quantitative method of current focus applying chromatography and mass spectrometry. Proteomic approaches to investigate lactational performance have made substantial findings especially in the alterations in lactation during mastitis. An experimental model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…cows and those with subclinical and clinical mastitis. Meanwhile, other authors reported that during natural inflammatory infections with Streptococcus agalactiae (Pongthaisong et al 2016), S. uberis (Eckersall 2019), and Serratia marcescens (Addis et al 2016) cathelicidin levels increase, and even suggested that this increase might serve as a biomarker for determining the stage of infection in dairy cows (Addis et al 2017). Wollowski et al (2021) measured cathelicidin in the milk samples from healthy cows and those with subclinical mastitis and showed that cathelicidin was found only in a half of cows with mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…cows and those with subclinical and clinical mastitis. Meanwhile, other authors reported that during natural inflammatory infections with Streptococcus agalactiae (Pongthaisong et al 2016), S. uberis (Eckersall 2019), and Serratia marcescens (Addis et al 2016) cathelicidin levels increase, and even suggested that this increase might serve as a biomarker for determining the stage of infection in dairy cows (Addis et al 2017). Wollowski et al (2021) measured cathelicidin in the milk samples from healthy cows and those with subclinical mastitis and showed that cathelicidin was found only in a half of cows with mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…u malih životinja na zarazne i neoplastične bolesti (Henry, 2010., Eckersall i McLaughlin, 2011., Humenik i sur., 2019.). Još je u povojima primjena proteomike u istraživanju laktacijskih parametara u goveda, ali već može pružiti određeni uvid u promjene nastale tijekom razvoja patoloških stanja te koristiti u fiziološkim i nutritivnim istraživanjima laktacije (Eckersall, 2019.). Najnovije proteomske tehnologije koriste se i za proučavanje biologije parazita, primjerice, helminta trematoda (Sotillo i sur, 2019.…”
Section: G) Primjena Metoda Ngs U Proteomici žIvotinjaunclassified
“…With regard to mastitis, not only the advancement in proteomic but also metabolomics approaches in milk are compiled in a further review focusing on Streptococcus uberis infection as an experimental model. The identification of proteins and metabolites being up-or down-regulated in infected versus healthy animals is elucidating the defence reactions and extends our knowledge about factors that are relevant in this context (Eckersall, 2019).…”
Section: Old and New Indicators In Milk For Health Status And Metabolmentioning
confidence: 99%